Transcatheter management of proximal stent migration in coarctation of the aorta - Diogo Remi Oliveira Faim; Patrícia Vaz Silva; Andreia Francisco; António Pires (Wolters Kluwer Medknow Publications, 2022)
Proximal stent migration in setting of transcatheter management of coarctation of the aorta is a rare complication, which may require emergency surgery. Herein, we report a successful transcatheter management of proximal stent migration in a high surgical risk, a 14-year-old girl, which caused partial occlusion of both the descending aorta and the left subclavian artery.